Rhinitis sicca anterior in children: epidemiology and treatment with sesame seed oil nasal spray - Fedyr Yurochko (Publishing House Zaslavsky, 2021)
Excessive dryness in the nose is very common among the population. The diagnosis of rhinitis sicca anterior is established quite often. Therefore, such patients need multicomponent treatment, taking into account all possible factors. The objective of this study was to investigate the effectiveness of sesame seed oil nasal spray (Sezorin manufactured by JSC “Farmak”) in rhinitis sicca anterior among children. As a result of using this drug, we achieved a fairly rapid and sustained reduction in clinical symptoms in our patients, and it is important to note that the effect of treatment with Sezorin spray was long-lasting.